A wandering fish bone. Issue 967 (5th May 2006) - Patel, V M; Barai, R S; Thomas, P R
Abstract : A unique case is described of an ingested fish bone migrating into the common hepatic duct, without perforation. Most foreign bodies are known to pass through the gastrointestinal tract uneventfully. Sharper objects such as fish bones have been known to cause perforation. This is more common, in countries where fish consumption is considerably higher, such as, south east Asia. However, even in these regions there have been no reports of such a proximal migration.